Efeitos de diferentes histórias experimentais sobre o comportamento de seguir regras em participantes classificados de flexíveis e inflexíveis - SOUZA, Lívia Mello (2008)
The present study investigated wether the maintenance or not of the behavior of following discrepant rules of programmed contingencies of reinforcement in an experimental situation depends more on the listeners experimental history or his pre-experimental history, inferred by his answers to a questionnaire about unflexibility. Sixteen college students previously selected on the basis of their answers in a questionaire about unflexibility, were exposed to a procedure of choice according to sample. In each attempt, a model stimulus and three comparison stimuli were presented to the participant, which had to point to the three comparison ones, in a predetermined sequence. The participants were assigned to two conditions, and each condition had four phases. The conditions differed only by the schedule of reinforcement applied. In Condition 1, the schedule of reinforcement was continous (CRF) and in Condition 2 it was fixed-rate (FR4). In both conditions, Phase 1 began with the presentation of minimal instructions and a sequence of responses was established by diferential reinforcement; Phase 2 began with the presentation of a discrepant rule; Phase 3 began with the presentation of a correspondent rule; and Phase 4 began with the representation of the discrepant rule. Eight participants (four classified as flexible and four classified as unflexible) were exposed to Condition 1 (CRF) and eight participants (four classified as flexible and four classified as unflexible) were exposed to Condition 2 (FR4). Results show that apart from the classification, the eight participants in Condition 1 abandoned rule-following that was discrepant from the contingencies, pointing that the control exercised by the constructed experimental history prevented the observation of preexperimental variables upon the participants behavior of following discrepant rules. The results of Condition 2 showed that the four participants classified as flexible abandoned following the discrepant rule and the four participants classified as unflexible maintained the rule-following that was discrepant from the contingencies, ponting that under these conditions, control by different pre-experimental histories prevailed. Comparing the results in both conditions it can be summarized that the maintenance of the behavior of following discrepant rules does not depend only on the experimental or pre-experimental history of the listener, but depends on the combination of a number of conditions favorable or unfavorable to the maintence of the behavior of following a discrepant rule.